MADIN PROGRAM FOR STUDENTS AS A TRANSFORMATIVE ISLAMIC EDUCATION MODEL FOR AGAINST RADICALISM AND TERRORISM - Arifuddin, Nur; Nurcholis, Ahmad; Hidayatullah, Syaikhu Ihsan; Timbul, Timbul; Rudisunhaji, Muhamad Asngad (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2024)
ABSTRACT This research examines the implementation of the Madrasah Diniyah program at UIN Satu Tulungagung as a model of Transformative Islamic education to prevent radicalism and terrorism. It used a qualitative approach, focusing on paradigms, strategies, and qualitative models. The grand theory of this study is Berkowitz's